Promotion Event Application Revolution ( P.E.A.R ) - Supian, Muhammad Danial Nadzif (IRC, 2019)
Marketing the promotion event that been held is a crucial strategies of business world as it is one of the crucial method that help the company to increase their profitability of product and services. The goal of marketing is to own the market, not just selling the product as it’s a remedy of companies that adopt a limiting market share mentality. As we know, when we own the market, we lead the market. Therefore, the company need to choose wisely on their medium to announce the promotion event to their customer out there or otherwise it will lead chaos to the company financial performance. It is undeniable that there are various way to make announcement to the customer such as through email, Facebook, television advertisement and etc. As time goes by, the current method is not very effective to customer as they sometimes received the promotion news at the last minutes. Besides that, they also have to spend time on go one by one of the retailers business website in order to discover promotion event. This will improve the efficiency and catering for these problems through the development of a new centralized system to collect all promotional events for clothes retailers in Malaysia. The development of the system uses the standard cycle of life for development. There are two solutions to the program itself, one being the website, and one being the Android software. The collected data is saved in the SQL database. This program will therefore bring some benefits to everybody, including the consumer and the suppliers, as this will improve the level of communication and understanding.